The Influence Of Transformatıonal Leadershıp Style And Job Satısfactıon On Work Engagement Through Perceıved Organızatıonal Support At CV Rafana Kıds Store - Taufiq Rachman; Fitri Rezeki (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study explores the interrelations among organizational culture, perceived organizational support, transformational leadership, and work engagement. Using a robust statistical framework, the research examines how these variables interplay and influence one another, thereby affecting employee performance and job satisfaction. Organizational culture was found to have a significant predictive power over perceived organizational support, but its direct influence on work engagement was less pronounced, necessitating a mediator such as perceived support. Perceived organizational support robustly mediated the relationship between organizational culture and work engagement, emphasizing the necessity for employees to feel valued and supported. Transformational leadership had a nuanced impact; it directly influenced work engagement marginally, yet did not significantly affect perceived organizational support nor work engagement indirectly through perceived organizational support. These findings suggest that transformational leadership may require additional mediating factors to effectively promote engagement. The study's indirect pathway analysis highlights that the pathway from organizational culture to work engagement through perceived organizational support is significant, confirming the mediating role of perceived support. Conversely, transformational leadership’s indirect impact on work engagement through perceived support was non-significant, indicating the potential need for other mediating variables. Conclusively, the research provides insights into the complex dynamics of workplace variables, stressing the importance of a holistic organizational approach to enhance employee engagement and performance. It also underscores the critical nature of employees' perceptions of support in translating leadership and cultural values into engagement.